A decade of evolving composites: regression- and meta-analysis. Issue 4 (9th November 2015) - Frowd, Charlie D.; Erickson, William B.; Lampinen, James M.; Skelton, Faye C.; McIntyre, Alex H.; Hancock, Peter J.B.
Abstract : Purpose: – The purpose of this paper is to assess the impact of seven variables that emerge from forensic research on facial-composite construction and naming using contemporary police systems: EvoFIT, Feature and Sketch. Design/methodology/approach: – The paper involves regression- and meta-analyses on composite-naming data from 23 studies that have followed procedures used by police practitioners for forensic face construction. The corpus for analyses contains 6, 464 individual naming responses from 1, 069 participants in 41 experimental conditions. Findings: – The analyses reveal that composites constructed from the holistic EvoFIT system were over four-times more identifiable than composites from "Feature" (E-FIT and PRO-fit) and Sketch systems; Sketch was somewhat more effective than Feature systems. EvoFIT was more effective when internal features were created before rather than after selecting hair and the other (blurred) external features. Adding questions about the global appearance of the face (as part of the holistic-cognitive interview (H-CI)) gives a valuable improvement in naming over the standard face-recall cognitive interview (CI) for all three system types tested. The analysis also confirmed that composites were considerably less effective when constructed from a long (one to two days) compared with a short (0-3.5 hours) retention interval. Practical implications: – Variables were assessed that are of importance to forensic practitioners who construct composites with witnesses and victims of crime. Originality/value: – Using a large corpus of forensically-relevant data, the main result is that EvoFIT using the internal-features method of construction is superior; an H-CI administered prior to face construction is also advantageous (cf. face-recall CI) for EvoFIT as well as for two further contrasting production systems.